Prenatal Relocation Stress Enhances Resilience Under Challenge in Infant Rhesus Macaques - Ceniceros, Lesly C.; Capitanio, John P.; Kinnally, Erin L. (Frontiers in Behavioral Neuroscience, 2021)
The prenatal period is a developmental stage of peak sensitivity, during which environmental exposures can program postnatal developmental outcomes. Prenatal stress, in particular, has often been associated with detrimental neurobehavioral outcomes like mood and anxiety disorders. In the present study, we examined the effects of a stressful prenatal maternal experience (maternal relocation during pregnancy) on the postpartum development of offspring in rhesus macaques. To help isolate the effects of prenatal stress from genetic predispositions and postnatal experience, we compared biologically reared infants (infants raised with their biological mothers) with cross-fostered infants (those raised by non-related females in new social groups). We examined the effects of prenatal relocation stress on measures collected at 3-4 months of age during a standardized biobehavioral assessment. Unexpectedly, we found that prenatal stress resulted in a behavioral pattern consistent with resilience rather than anxiety: prenatal stress was linked with greater activity, lower anxiety, and more interaction with novel objects, as well as higher ratings of temperamental confidence during assessment. These effects were observed in infants reared by biological mothers as well as cross-fostered infants, suggesting that the effects of prenatal stress were not attributable to maternal genetics or postnatal factors. Our surprising results suggest that prenatal relocation stress may confer resilience in infant rhesus monkeys.